THE IMPORTANCE OF RAILWAY CONSTRUCTION IN THE ECONOMY OF THE BUKHARA EMIRATE - Raykhona Mekhmonkulova (Ecominds Press, 2025)
This article explores the significance of railway construction in the economic development of the Bukhara Emirate during the late 19th and early 20th centuries. It analyzes how the establishment of railways contributed to the growth of trade, the expansion of markets, and the integration of the emirate into regional and international economic systems. The study also highlights the social and political implications of railway development, including the influence of Russian imperial policies and the modernization of transportation infrastructure. By examining historical sources and economic data, the article provides a comprehensive understanding of the transformative role of railways in the Bukhara Emirate’s economy.
Keywords: Bukhara Emirate, railway construction, economic development, trade, modernization, Russian Empire, Central Asia, infrastructure.